Efficacy of angiotensin receptor neprilysin inhibitor in Asian patients with refractory hypertension - Li, Wanjing; Gong, Minghui; Yu, Qin; Liu, Rihui; Chen, Kaiming; Lv, Wei; Yao, Fumei; Xu, Zhaolong; Xu, Yi; Song, Wei; Jiang, Yinong (The journal of clinical hypertension (Greenwich, Conn.), 2022)
Sacubitril/valsartan, simultaneously inhibits neprilysin and angiotensin II receptor, showed an effect in reducing blood pressure (BP). The authors aimed to study whether it can be used as an antihypertensive agent in patients with refractory hypertension who have already been treated. A total of 66 Chinese patients with refractory hypertension were enrolled. Patients received sacubitril/valsartan  200 instead of angiotensin II receptor blocker or angiotensin converting enzyme inhibitor while other agents continued. If BP was uncontrolled after 4 weeks, sacubitril/valsartan was increased to 400 mg. The BP reduction was evaluated by office BP and ambulatory BP monitoring after 8‐week treatment. The baseline office BP and mean arterial pressure (MAP) were 150.0/95.0 mmHg and 113.3 mmHg. BP and MAP reduced to 130.6/83.2 mmHg and 99.0 mmHg at week 8. Office BP and MAP reductions were 19.4/11.8 mmHg and 14.3 mmHg at endpoint (all p < .001). The 24‐h, daytime and nighttime ambulatory BP were 146.2/89.1, 148.1/90.3, and 137.5/83.7 mmHg, respectively at baseline, and BP reduced to 129.6/79.8, 130.6/81.1, and 121.7/75.8 mmHg, respectively at week 8. The 24‐h, daytime and nighttime ambulatory BP reductions were 16.6/9.3, 17.5/9.2, and 15.8/7.9 mmHg, respectively at endpoint (all p < .001). Sacubitril/valsartan significantly reduced office and ambulatory BP in refractory hypertension patients. Our study provided new evidence for sacubitril/valsartan in refractory hypertension.